Automorphisms of groups of order $p^5$ - Pechenyuk, О. V.; Pylyavs'ka, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study automorphisms of groups of order $p^5$ (p is an odd prime number). Groups without any automorphism of order 2 and groups with group automorphisms of order $p^6$ are found.